Ensino de sociologia: repensando práticas pedagógicas a partir da Lei da Reforma do Ensino Médio e da LDB n. 9.394/96 - Galvão, Emília Luenna Palhano (2022)
Considering the Law 13.415/17 that deals with the implementation of the new curricular organization of high school, we analyzed the reflexes of a curriculum structured in five Formative Itineraries and in the National Common Curriculum Base. We are willing to identify the theoretical-methodological strategies of the teaching of Sociology inherent to the current educational demands, in order to understand the correlation between the teaching of Sociology and the human formation of the student, seeking to value their social and cultural characteristics. Our methodological support is in qualitative research with an intersection in Cultural Studies, supported by the post-structuralist perspective. It is a social research that sought to oppose a normalizing education and the strengthening of the school within cultural pedagogies, and which welcomed documentary research as a method of procedure. We are experiencing an austere moment, the legislation for New High School as a power device, has preached the maxim of directing the student to the market and the world of work, following the orders and courses of capital. Unfortunately, human training has been dispensed with at the conclusion of the basic cycle, unwilling to actually carry out the integral training of this subject. The comings and goings of the discipline to the classrooms have brought countless challenges to the Social Sciences. Power relations constitute the Reform process as a whole, and are imprinted in the interconnections between the socio-historical context and its reproductions in the economic sphere. The discussions developed here intensified the construction of a pedagogical proposal aimed at the Centro de Ensino Educa Mais, state educational institutions in São Luís (MA), which pass through this moment of integralization of education. We estimate that the importance of Sociology in the school environment and in the dimension of human formation will rise, allowing the Sociology teacher to create spaces to resist the erasure of the discipline in the diversified part of the curriculum, although it is still facing the arbitrary constraints conferred on the educational scenario in the current plot Brazilian.